Neanderthals in the desert? Population history best explains Middle Palaeolithic technological heterogeneity in Arabia - James Blinkhorn; Huw S. Groucutt; W. Christopher Carleton; Eric Andrieux; Simon J. Armitage; Ceri Shipton; Paul S. Breeze; Nick Drake; Abdulaziz Al-Omari; Faisal Al-Jibreen; Abdullah M. Alsharekh; Eleanor M.L. Scerri; et al. (Quaternary Science Reviews, 2026)

Adaptive area-wide management for suppressing spruce budworm outbreaks: effectiveness of the early intervention strategy - Rob C. Johns; S. Edwards; L. Amos-Binks; J. J. Bowden; D. Carleton; C. Edge; C. Hennigar; P. James; D. MacLean; V. Martel; E. R. D. Moise; B. Morin; et al. (Journal of Pest Science, 2026)
In eastern North America, two main insecticide-based strategies are used to manage spruce budworm ( Choristoneura fumiferana ) outbreaks. The traditional ‘Foliage Protection Strategy’ (FPS) focuses on temporarily reducing defoliation and tree mortality in high-value stands, allowing outbreaks to progress naturally in surrounding areas. The ‘Early Intervention Strategy’ (EIS) is an adaptive, area-wide management approach that targets low-density “hotspots” to prevent outbreak growth and spread. We report findings from a 10-year case study (2015–2024) in Atlantic Canada assessing EIS effectiveness. EIS treatments consistently reduced population growth rates, resulting in a 12–67% reduction in hotspot areas compared to untreated areas. Crucially, this suppression curbed the rise and spread of the outbreak across northern New Brunswick, with negligible defoliation observed throughout the study period. By comparison, in a neighboring Quebec study area contemporaneously managed with FPS, the outbreak advanced normally, causing moderate to severe defoliation over ~ 1.7 million hectares by 2024. Moreover, EIS required ~ 80% less insecticide, with 66% of treated areas receiving treatment in only a single year, compared with just 15% under FPS. Our findings provide robust evidence for the effectiveness of EIS when implemented under suitable conditions, highlighting its potential as a proactive outbreak management approach.

Differential advances in budburst timing among black spruce, white spruce and balsam fir across Canada - Diego S. Podadera; Lorena Balducci; Sergio Rossi; Fabrizio Cartenì; Valérie Néron; Rémi Saint-Amant; Stefano Mazzoleni; Jacques Régnière; Eric R.D. Moise; Joseph J. Bowden; Jean-Noël Candau; Alain Dupont; et al. (Agricultural and Forest Meteorology, 2024)

Nutrient explorer: An analytical framework to visualize and investigate drivers of surface water quality - Michael J. Pennino; Meridith M. Fry; Robert D. Sabo; James N. Carleton (Environmental Modelling & Software, 2023)

Interannual, sub-seasonal and spatial variations in growing season surface heat fluxes for the U.S. Corn Belt - Mikael P. Hiestand; Andrew M. Carleton; Kenneth J. Davis (Agricultural and Forest Meteorology, 2023)

Comparison of Titer and Signal to Noise (S/N) for Determination of Anti-drug Antibody Magnitude Using Clinical Data from an Industry Consortium - Marta Starcevic Manning; Mohamed Hassanein; Michael A. Partridge; Vibha Jawa; Johanna Mora; Josiah Ryman; Breann Barker; Christian Braithwaite; Kevin Carleton; Laura Hay; Charles Hottenstein; Robert J. Kubiak; et al. (The AAPS Journal, 2022)
During biotherapeutic drug development, immunogenicity is evaluated by measuring anti-drug antibodies (ADAs). The presence and magnitude of ADA responses is assessed using a multi-tier workflow where samples are screened, confirmed, and titered. Recent reports suggest that the assay signal to noise ratio ( S / N ) obtained during the screening tier correlates well with titer. To determine whether S / N could more broadly replace titer, anonymized ADA data from a consortium of sponsors was collected and analyzed. Datasets from clinical programs with therapeutics of varying immunogenicity risk levels (low to high), common ADA assay platforms (ELISA and MSD) and formats (bridging, direct, solid-phase extraction with acid dissociation), and titration approaches (endpoint and interpolated) were included in the analysis. A statistically significant correlation between S / N and titer was observed in all datasets, with a strong correlation (Spearman’s r > 0.8) in 11 out of 15 assays (73%). For assays with available data, conclusions regarding ADA impact on pharmacokinetics and pharmacodynamics were similar using S / N or titer. Subject ADA kinetic profiles were also comparable using the two measurements. Determination of antibody boosting in patients with pre-existing responses could be accomplished using similar approaches for titer and S / N . Investigation of factors that impacted the accuracy of ADA magnitude measurements revealed advantages and disadvantages to both approaches. In general, S / N had superior precision and ability to detect potentially low affinity/avidity responses compared to titer. This analysis indicates that S / N could serve as an equivalent and in some cases preferable alternative to titer for assessing ADA magnitude and evaluation of impact on clinical responses. Graphical Abstract

Can Anti-Metastatic Albumin-based Superoxide Dismutase Mimetic Serve as a “Moonshot” Drug for Treatment for Brain Tumors - From Medulloblastoma to Glioblastoma? - Carleton J. C. Hsia; Shanta M. Messerli; W. Keith Miskimins (Cell Biochemistry and Biophysics, 2019)

Can Macromolecular Nitroxide Work as Extracellular Superoxide Dismutase Mimetic in Cancer and Stroke Therapy? - Carleton J. C. Hsia; W. Keith Miskimins (Cell Biochemistry and Biophysics, 2018)

Why UV vision and red vision are important for damselfish (Pomacentridae): structural and expression variation in opsin genes - Sara M. Stieb; Fabio Cortesi; Lorenz Sueess; Karen L. Carleton; Walter Salzburger; N. J. Marshall (Molecular Ecology, 2017)
Coral reefs belong to the most diverse ecosystems on our planet. The diversity in coloration and lifestyles of coral reef fishes makes them a particularly promising system to study the role of visual communication and adaptation. Here, we investigated the evolution of visual pigment genes (opsins) in damselfish (Pomacentridae) and examined whether structural and expression variation of opsins can be linked to ecology. Using DNA sequence data of a phylogenetically representative set of 31 damselfish species, we show that all but one visual opsin are evolving under positive selection. In addition, selection on opsin tuning sites, including cases of divergent, parallel, convergent and reversed evolution, has been strong throughout the radiation of damselfish, emphasizing the importance of visual tuning for this group. The highest functional variation in opsin protein sequences was observed in the short‐ followed by the long‐wavelength end of the visual spectrum. Comparative gene expression analyses of a subset of the same species revealed that with SWS 1, RH 2B and RH 2A always being expressed, damselfish use an overall short‐wavelength shifted expression profile. Interestingly, not only did all species express SWS 1 – a UV ‐sensitive opsin – and possess UV ‐transmitting lenses, most species also feature UV ‐reflective body parts. This suggests that damsels might benefit from a close‐range UV ‐based ‘private’ communication channel, which is likely to be hidden from ‘ UV ‐blind’ predators. Finally, we found that LWS expression is highly correlated to feeding strategy in damsels with herbivorous feeders having an increased LWS expression, possibly enhancing the detection of benthic algae.

Investigating interactions between phentermine, dexfenfluramine, and 5-HT2C agonists, on food intake in the rat - Andrew J. Grottick; Kevin Whelan; Erin K. Sanabria; Dominic P. Behan; Michael Morgan; Carleton Sage (Psychopharmacology, 2015)

Potential for Southern Hemisphere climate surprises - P. A. MAYEWSKI; T. BRACEGIRDLE; I. GOODWIN; D. SCHNEIDER; N. A. N. BERTLER; S. BIRKEL; A. CARLETON; M. H. ENGLAND; J‐H. KANG; A. KHAN; J. RUSSELL; J. TURNER; et al. (Journal of Quaternary Science, 2015)
Climate model results suggest that future climate change in Antarctica will be accompanied by continued strengthening and poleward contraction of the Southern Ocean westerly wind belt. Paleoclimate records suggest past changes in the westerly winds can be abrupt and that healing of the Antarctic ozone hole could lead to poleward contraction of the westerlies and increased meridional atmospheric transport of warm air regionally into Antarctica. An abrupt shift to more meridional circulation could lead to notable changes in moisture availability for extra‐Antarctic regions, increased Antarctic ice sheet disintegration and more rapid sea‐level rise.

Mercury proxies and mercury dynamics in a forested watershed of the US Northeast - P. Vidon; W. Carleton; M. J. Mitchell (Environmental Monitoring and Assessment, 2014)

Evolution of the ABPA Subunit of Androgen-Binding Protein Expressed in the Submaxillary Glands in New and Old World Rodent Taxa - Michael W. Vandewege; Carleton J. Phillips; Jeffrey K. Wickliffe; Federico G. Hoffmann (Journal of Molecular Evolution, 2013)

Surface radar-derived convective rainfall associations with Midwest US land surface conditions in summer seasons 1999 and 2000 - Corene J. Matyas; Andrew M. Carleton (Theoretical and Applied Climatology, 2010)

Zooplankton In An Australian Tropical Estuary - S. Duggan; A. D. McKinnon; J. H. Carleton (Estuaries and Coasts, 2008)

US jet contrail frequency changes: influences of jet aircraft flight activity and atmospheric conditions - David J. Travis; Andrew M. Carleton; Jeffrey S. Johnson; James Q. DeGrand (International Journal of Climatology, 2007)
In the United States, the dramatic increase in jet fuel usage and kilometers flown has led to speculation of a similar increase in jet contrails. However, contrail occurrence depends heavily upon the meteorological conditions near cruising altitudes (i.e. the tropopause, 10–12 km altitude). This study reports a contrail mid‐season contemporary climatology for the coterminous United States (2000–2002), and compares the frequencies with those previously reported for an earlier (1977–1979) period, to determine spatial and seasonal contrail frequency changes. For both climatologies, contrail occurrence is derived from the analysis of high‐resolution satellite imagery. Data on US jet aircraft flight activity were obtained to assess their relationship to contrail frequency, as were NCEP‐NCAR reanalysis data to determine the changes in tropopause‐level atmospheric conditions. For the 2000–2002 period, contrails comprise a distinct high (low) frequency pattern in the East (West) halves of the United States. Seasonally, there is a contrail association with the latitudinal migration of the jet stream and a US‐wide peak contrail frequency during winter (January). The inter‐monthly variations in contrail frequency are significantly different from each other but show no association with variations in jet flight activity, indicating a greater role for meteorological conditions. Between the 1977–1979 and 2000–2002 periods, there were strong spatial and seasonal asymmetries to the contrail frequency change. These involve a cooling (warming) of the tropopause for the largest (smallest) frequency increases, which shows some association with the switch in positive and negative phases of the Arctic Oscillation. The role of upper tropospheric conditions and links to hemispheric‐scale teleconnections should be considered when projecting contrail frequency changes and their future impacts on climate. Copyright © 2006 Royal Meteorological Society

Turbulent mixing and mesoscale distributions of late‐stage fish larvae on the NW Shelf of Western Australia - M. G. MEEKAN; J. H. CARLETON; C. R. STEINBERG; A. D. MCKINNON; R. BRINKMAN; P. J. DOHERTY; A. HALFORD; S. DUGGAN; L. MASON (Fisheries Oceanography, 2006)
Light traps were deployed to describe vertical and cross‐shelf distributions of late‐stage larval fishes during five cruises in each of the 1997/98 and 1998/99 summers in the region of the Gulf of Exmouth on the southern North West Shelf of Western Australia. At each light trap station on a cross‐shelf transect we measured water temperature, salinity and chlorophyll a and used vertical plankton tows to estimate zooplankton biomass and copepod abundance. Current meters were deployed on moorings near the transect and the data used to model flows and mixing on the NW Shelf and in the Gulf. The majority of reef, pelagic and baitfish larvae (81, 83 and 66% respectively) were collected at only two stations that marked the boundary between stratified waters offshore and well‐mixed water within the Gulf. Most baitfishes (primarily Spratelloides spp.) were captured by traps deployed near the seabed, while reef fishes (mostly pomacentrids, lethrinids and siganids) and pelagic species (mostly scombrids and carangids) were captured in traps deployed near surface. Catch composition varied between summers with 64% of baitfishes collected in the first summer, while the majority of reef and pelagic fishes (81 and 80% respectively) were captured in the second summer. Modelling of circulation showed that the velocity of tidal currents was enhanced by constriction of flow between NW Cape and South Muiron Island and by shallowing of the shelf. Flood‐tide intrusions of water allowed the thermocline to move up the continental shelf, upwelling cool nutrient‐rich water that was then mixed throughout the entire water column at stations in the mouth of the Gulf. This upwelling and mixing resulted in higher chlorophyll a concentrations and copepod abundances either as a result of local in situ growth or advection/aggregation processes, and may account for the great abundances of late‐stage fish larvae in the mouth of the Gulf.

Antarctic climate change during the last 50 years - John Turner; Steve R. Colwell; Gareth J. Marshall; Tom A. Lachlan-Cope; Andrew M. Carleton; Phil D. Jones; Victor Lagun; Phil A. Reid; Svetlana Iagovkina (International Journal of Climatology, 2005)

Estimating the patch size of larval fishes during colonization on coral reefs - D. Lecchini; V. Dufour; J. Carleton; S. Strand; R. Galzin (Journal of Fish Biology, 2004)
Fish larvae were sampled daily over a period of 14 days using six crest nets spaced at 200 m intervals on a coral reef on the west coast of Moorea Island, French Polynesia, to estimate the extent to which ichthyonekton arriving at one location reflected ichthyonekton arriving at neighbouring areas. Each night, the six crest nets were colonized by larval fishes from the same location.

Population variation in opsin expression in the bluefin killifish, Lucania goodei : a real-time PCR study - R. C. Fuller; K. L. Carleton; J. M. Fadool; T. C. Spady; J. Travis (Journal of Comparative Physiology A, 2004)

Rational Forest Productivity Decline - James I. MacLellan; T. J. Carleton (Environmental Monitoring and Assessment, 2003)

Zooplankton community structure and water flow in the lee of Helix Reef (Great Barrier Reef, Australia) - Carleton J.; Brinkman R.; Doherty P. (Marine Biology, 2001)

Changing Species Richness and Composition in Canadian National Parks - Donald H. Rivard; Jean Poitevin; Daniel Plasse; Michel Carleton; David J. Currie (Conservation Biology, 2000)
Canada's national parks and their surrounding areas differ markedly in size, climate, vegetation, and extent of human development. We tested the extent to which total species richness, native species richness, and the number of extirpations and introductions of terrestrial vertebrates were correlated with each of these factors. To do this, we used surveys of park fauna from the present and from the time of park establishment. Richness, extirpations, and introductions were all strongly related to climate. After we controlled for climate, smaller parks had higher rates of species loss than larger parks. Land‐use patterns (forest cover and fragmentation, roads, etc.) within parks were strongly correlated with land use in the regions surrounding the parks, showing that parks have not been isolated from regional development. Richness and extirpations within parks were generally more strongly related to regional characteristics than to the characteristics of the parks themselves. Species richness and numbers of introduced species were higher in parks found in landscapes with greater fragmentation. Frequencies of extirpations were less clearly related to human‐influenced habitat characteristics. Introductions and extinctions most often involved game species or species directly associated with human activities. There is little evidence of subtle ecological effects being responsible for species loss. Our results suggest that management should focus on direct human interventions, such as hunting, introduction of game species, and habitat fragmentation, in parks and surrounding areas.

Tropical zooplankton in the highly-enclosed lagoon of Taiaro Atoll (Tuamotu Archipelago, French Polynesia) - J. H. Carleton; P. J. Doherty (Coral Reefs, 1998)

Prediction of reproductive success and failure in lesser snow geese based on early season climatic variables - W. R. Skinner; R. L. Jefferies; T. J. Carleton; R. F. Rockwell&dagger K. F. Abraham (Global Change Biology, 1998)
The North American mid‐continent population of lesser snow geese ( Anser caerulescens caerulescens ) breeds in coastal areas of the Hudson Bay region. Breeding success is highly variable, particularly during recent decades. The availability of long‐term data sets of weather and the breeding success of geese allowed us to determine whether climatic variables in spring and early summer (May–June) are reliable predictors of different attributes of the reproductive biology of snow geese. A large region of strong anomalous cooling in north‐eastern North America has been the dominant anomalous climatic feature since the mid‐1970s. The cooling which becomes established during winter persists into spring and early summer when migration, nesting and hatching of geese are occurring. Redundancy analysis (RDA) of the data sets was made to identify dominant correlations and regression relationships between climatic and goose variables. Individual goose response variables were further explored with stepwise multiple regression and bipartial regression. 96.7% of year‐to‐year variance in the goose data was explained by the selected climatic data. The first four orthogonal axes out of seven possible axes explained 92.2% of the total variance. Date of last snow on the ground and mean daily temperature from 6 to 20 May formed the lowest and highest predictor scores, respectively. Initiation date and hatching date at the low end and total clutch size and clutch size at hatch at the high end were associated with these extremes, particularly in certain years. Days of freezing rain in May and total rainfall were correlated with nest failure. Bivariate correlation/regression showed that the most parsimonious model for nest initiation day was based on four climatic predictors, for hatching day four predictors, and for clutch size at hatch, nine predictors. Both the multiple regression analyses and the redundancy analyses confirm the high degree of predictability of goose reproductive variables from selected climatic variables. As discussed, the correlations reflect both direct and indirect effects of climate on the reproductive biology of geese. The correlations are strongest in the early season and weaken by early summer.